Effects of anti-rainbow trout germ-cell monoclonal antibody on germ cells and gonadal tissues in rainbow trout (Oncorhynchus mykiss) - Kenji, Takase; Akihiro, Harakawa; Masaki, Yokota; Lau, Lik Ming; Yuichi, Amano; Kensuke, Ichida; Keiichiro, Koiwai; Ikuo, Hirono; Hidehiro, Kondo (Elsevier B.V., 2025)
The development of sterilization technology is important to improve the production efficacy of aquaculture and prevent genetically modified fish from escaping. Immunosterilization is a novel sterilization method that has already been used in mammals. In this study, anti-rainbow trout germ-cell monoclonal antibodies (anti-GC mAbs) were injected into immature rainbow trout Oncorhynchus mykiss, and their effects were analyzed. First, anti-GC mAbs labeled with Alexa Fluor 488 were injected into the body cavity of larvae 20 days (group 1) and 102 days (group 2) after fertilization. Second, anti-GC mAbs were injected into the body cavity of yearling trout (group 3), and their impacts on gonadal tissue were analyzed in terms of histology and gene expression levels. As a result, anti-GC mAbs were observed to bind to some primordial GCs in group 1, whereas there were no obvious positive cells in male testes of group 2. In contrast, green fluorescent signals were observed in an arrangement parallel to the ovarian lamina in female ovaries of group 2, which was similar to the arrangement of positive signals on ovarian tissue sections immunostained with anti-GC mAbs. GCs in group 1 were observed again after 76 days, and double-positive cells remained. In group 3, there were changes in the expression levels of GC-specific genes, but the changes were not seen as biologically meaningful. Moreover, there was no histological abnormality in gonadal tissues after immunization. In conclusion, these results suggested that anti-GC mAbs could only reach GCs in early developmental stages or in the ovary, and injection of anti-GCs mAbs did not have harmful effects on GCs after binding.